Chair - Conference Program Chair - Michael-Grigoriou, Despina (My University, 2026)
Conference Lead Program Chair: coordinate the whole process and all its tasks with the support of the other co-chairs: call for papers, forming the IPC, reviewers allocations, decisions on the rebuttal process, final decisions, notifications to authors, conference program in regards to the papers presentations, etc.